Major Challenges for Economic Growth and Poverty Reduction in the Mekong River Delta - World Bank (Washington, DC, 2013)
The study focuses on analyzing and assessing some main features of the situation and the implementation results of Comprehensive Poverty Reduction and Growth Strategy (CPRGS) in order to identify major challenges for economic growth and poverty reduction, which will serve as the basis for the proposal of policy framework to overcome the challenges as well as achieve the basic targets for economic growth and poverty reduction in the Mekong River Delta (MRD). This analysis is put in the general context of the whole countries and the MRD's socio-economic development and in the interrelationship between sustainable economic growth and poverty reduction. The scope of the study in this stage focuses on the general problems and regional features of economic growth and poverty reduction.